A hybrid dry-fermentation and membrane contactor system: Enhanced volatile fatty acid (VFA) production and recovery from organic solid wastes - TUĞTAŞ KARNABAT, ADİLE EVREN; ÇALLI, BARIŞ; YEŞİL, HATİCE (PERGAMON-ELSEVIER SCIENCE LTD, 2021)
Anaerobic dry-fermentation of food wastes can be utilized for the production of volatile fatty acids (VFA). However, especially for high load fermentation systems, accumulation of VFAs may result in inhibition of fermentation process. In this study, separation of VFAs from synthetic mixtures via a vapor permeation membrane contactor (VPMC) system with an air-filled polytetrafluoroethylene (PTFE) membrane was assessed at various temperatures and permeate solution concentrations. In addition, a pioneering integrated leach-bed fermentation and membrane separation system was operated with undefined mixed culture for the purpose of enhanced VFA production along with its recovery. Hybrid system resulted in 42% enhancement in total VFA production and 60% of total VFAs were recovered through the VPMC system. The results of this study revealed that integrated system can be exploited as a means of increasing organic loading to fermentation systems and increasing the value of VFA production. (c) 2021 Elsevier Ltd. All rights reserved.
Keywords: Anaerobic; Carboxylate platform; Fermentation; Membrane; Separation; Short chain fatty acids